2021
DOI: 10.18502/ijhoscr.v15i3.6852
|View full text |Cite
|
Sign up to set email alerts
|

Hyperdiploid Multiple Myeloma with Novel Complex Structural Chromosome Abnormalities Associated with Poor Prognosis : A Rare Case Report

Abstract: Hyperdiploid multiple myeloma (MM) is associated with better prognosis and non-hyperdiploid subtype is associated with variable to adverse prognosis based on the nature of karyotype abnormality. Rarely exceptions to this hyperdiploid and non-hyperdiploid divisions do exist in a minority. We report an adult male MM patient who showed hyperdiploid karyotype with few novel complex abnormalities and who showed poor clinical outcome. Conventional cytogenetic analysis carried out in 22 GTG banded metaphases showed 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The most frequent type of abnormalities in MM is the CNV's (copy number variations). The duplication of odd chromosome (3,5,7,9,11,15,19,21) divides MM in hyperdiploid and non-hyperdiploid (Buedts, Smits et al 2020) and is found in around 50% of MM and confer a good prognosis (Fonseca, Barlogie et al 2004, Barilà, Bonaldi et al 2020, Ankathil, Foong et al 2021. The deletion of chr 1p has an incidence of approximatively 30% and give a poor prognosis especially if 1p32 is implicated (Qazilbash, Saliba et al 2007, Ouyang, Gou et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent type of abnormalities in MM is the CNV's (copy number variations). The duplication of odd chromosome (3,5,7,9,11,15,19,21) divides MM in hyperdiploid and non-hyperdiploid (Buedts, Smits et al 2020) and is found in around 50% of MM and confer a good prognosis (Fonseca, Barlogie et al 2004, Barilà, Bonaldi et al 2020, Ankathil, Foong et al 2021. The deletion of chr 1p has an incidence of approximatively 30% and give a poor prognosis especially if 1p32 is implicated (Qazilbash, Saliba et al 2007, Ouyang, Gou et al 2014.…”
Section: Introductionmentioning
confidence: 99%